2018
DOI: 10.1177/2309499018799534
|View full text |Cite
|
Sign up to set email alerts
|

Local implantation of autologous adipose-derived stem cells increases femoral strength and bone density in osteoporotic rats: A randomized controlled animal study

Abstract: Background: Deficient osteogenic capacity of bone marrow stem cells plays a critical role in the pathophysiology of osteoporosis. Adipose-derived stem cells (ADSCs) have emerged as a promising source of skeletal progenitor cells. The capacity of ADSCs to undergo osteogenic differentiation and induce mineralized tissue formation may be beneficial in the treatment of osteoporosis. We question whether administration of autologous ADSCs into the proximal femur of osteoporotic rats will induce osteogenesis and enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 26 publications
1
23
0
1
Order By: Relevance
“…In addition, a single intratibial injection of AMSCs significantly improved trabecular bone quality after 6 weeks in comparison to untreated contralateral bones [117]. Similar results were obtained by Uri et al in a study in which AMSCs- seeded scaffolds were implanted into the proximal femur of osteoporotic rats [114]. Results showed that the mean cortical thickness, bone volume density, and bone load to failure in AMSCs injected femora were higher compared to control group.…”
Section: Application Of Amscs In the Treatment Of Osseous Diseasessupporting
confidence: 54%
See 2 more Smart Citations
“…In addition, a single intratibial injection of AMSCs significantly improved trabecular bone quality after 6 weeks in comparison to untreated contralateral bones [117]. Similar results were obtained by Uri et al in a study in which AMSCs- seeded scaffolds were implanted into the proximal femur of osteoporotic rats [114]. Results showed that the mean cortical thickness, bone volume density, and bone load to failure in AMSCs injected femora were higher compared to control group.…”
Section: Application Of Amscs In the Treatment Of Osseous Diseasessupporting
confidence: 54%
“…Age-related skeletal changes, such as osteoporosis, are closely related to imbalanced bone remodeling characterized by elevated osteocyte apoptosis and osteoclast activation [114]. Recently, a study has demonstrated for the first time that AMSCs exosomes inhibits induced osteocyte apoptosis and osteocyte-mediated osteoclastogenesis [115].…”
Section: Application Of Amscs In the Treatment Of Osseous Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cell therapy of osteoporosis, ASCs have been reported as effective autologous cells. The mechanism of improving OVX‐induced osteoporosis is similar to that of BMMSCs, which is mainly reflected in three aspects: (a) Significant increases in cortical thickness, bone volume density and bone load 63 , (b) improved trabecular microstructure 64 , and (c) increased serum calcium and OCN levels 65 . Ye et al 66 revealed that osteogenic‐induced ASCs promoted osteogenesis and inhibited adipogenesis of osteoporotic BMMSCs by activating BMP‐2 signalling pathway, which explained above as an important pathway in osteogenic differentiation.…”
Section: Preclinical Investigationsmentioning
confidence: 99%
“…The Bichat ball has a large number of mesenchymal stem cells with great differentiation potential, in this way it is seen as a promising source of progenitor cells. A recent study [11] conducted experiments in animals with the aim of inducing the formation of mineralized tissue for the treatment of osteoporosis from cells derived from adipose tissue and the result was promising. In the case of an evolution of the studies in this sense, the use of the ball of Bichat, mainly for functional purposes, would gain even more relevance.…”
Section: Discussionmentioning
confidence: 99%